2008
DOI: 10.5694/j.1326-5377.2008.tb01749.x
|View full text |Cite
|
Sign up to set email alerts
|

The implementation and impact of different funding initiatives on access to multidisciplinary primary health care and policy implications

Abstract: Objective: To review the implementation and impact of different funding initiatives across the health systems of three different countries — England, New Zealand and Australia — on the achievement of multidisciplinary primary health care (PHC) and to reflect on policy implications for Australia. Methods: A systematic review of the literature involving three stages: (i) identification and description of initiatives; (ii) a systematic review of their implementation and impact from 1995 to mid 2006; and (iii) an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“… Chronic disease management ( Cranston et al, 6 Dennis et al 7 ); Integration, coordination and multidisciplinary care ( Jackson et al, 8 Mitchell et al, 9 Powell Davies et al 10 ); Innovative models for comprehensive primary health care delivery ( McDonald et al, 11 Naccarella et al, 12 Humphreys et al 13 ); Innovative models for the management of mental health in primary health care settings ( Griffiths and Christensen 14 ); Children and young Australians, health promotion and prevention ( McDonald et al, 15 Hearn et al 16 ); and Workforce (focus on competency‐based training) ( Glasgow et al 17 ). …”
Section: Streammentioning
confidence: 99%
“… Chronic disease management ( Cranston et al, 6 Dennis et al 7 ); Integration, coordination and multidisciplinary care ( Jackson et al, 8 Mitchell et al, 9 Powell Davies et al 10 ); Innovative models for comprehensive primary health care delivery ( McDonald et al, 11 Naccarella et al, 12 Humphreys et al 13 ); Innovative models for the management of mental health in primary health care settings ( Griffiths and Christensen 14 ); Children and young Australians, health promotion and prevention ( McDonald et al, 15 Hearn et al 16 ); and Workforce (focus on competency‐based training) ( Glasgow et al 17 ). …”
Section: Streammentioning
confidence: 99%
“…A recent systematic review of the literature on funding incentives and multidisciplinary team care found only two published studies that used experimental or quasi-experimental design, with the remainder being descriptive studies; the authors were unable to find firm evidence on whether or not financial incentives of themselves improve health outcomes [17]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common definition sees primary health as a level of care provided at the first entry point to the health system by mainly General Practitioners and possibly some Nursing or Allied Health staff [8] . Others have broadened this definition to include first line services that move beyond individual treatment to incorporate measures that are preventative and have a population focus [9] . Systematic reviews using this definition of CPHC have been undertaken with a focus on accessibility, financing [9] and the various models delivered to Australians living in rural and remote areas [10;11] .…”
Section: Introductionmentioning
confidence: 99%
“…Others have broadened this definition to include first line services that move beyond individual treatment to incorporate measures that are preventative and have a population focus [9] . Systematic reviews using this definition of CPHC have been undertaken with a focus on accessibility, financing [9] and the various models delivered to Australians living in rural and remote areas [10;11] . However, this narrative review undertaken as part of the RHFA project is the first to examine CPHC across Australia as the approach outlined in Alma Ata [1] incorporating not only first line medical and allied health care with a range from treatment to prevention but also the other key elements of equity of access, collaboration across sectors beyond health and consumer and community empowerment and participation in the services.…”
Section: Introductionmentioning
confidence: 99%